영어 학습부진아를 위한 문화이해중점 초등학교 방과후 영어 프로그램 효과 연구 - 박선호(Park, Seon-Ho); 주혜영(Joo, Hyeyoung) (영어교육연구, 2012)
This study investigates the effects of a special English program based on cultural understanding models for elementary school underachievers in English. Ten students with low grades in their English achievements were selected as subjects for the study. Two kinds of cultural understanding learning models, mainly based on Moran’s (2001) cultural experimental learning model, were used for the program. Findings revealed that the program using cultural understanding class models had positive influences on underachievers’ English ability by improving their achievement scores, vocabulary acquisition strategies, and self-directed interactions related with listening and speaking skills. The program was identified to have developed underachievers’ cultural understanding by making them increase their willingness to contact with other cultures, by allowing them to gain cultural knowledge, and by decreasing their cultural biases. In addition, the program influenced the underachievers positively in their affective domains by improving their learning interest and self-confidence. With the results from the study, some suggestions are made for the further development and the application of the program for the underachievers in English. KCI Citation Count: 8